The Relationship Between Sitting Position and Hypotension During Spinal Anesthesia Induction in Cesarean Section Patients with Cardiovascular Problems - Ni Nyoman Ari Kundari Dewi (GLOBAL HEALTH SCIENCE GROUP, 2025)
Hypotension in patients undergoing cesarean section is a dangerous medical condition during surgery. Appropriate treatment must be provided starting from pre-anesthesia planning. The patient's position during spinal anesthesia induction is the first step to successful anesthesia, so it is important to monitor it closely during the pre-, intra-, and post-anesthesia phases. The purpose of this study was to determine the relationship between sitting position and the incidence of hypotension during spinal anesthesia induction in cesarean section patients at Kasih Ibu Hospital in Denpasar. This study used a correlational analytical approach with a cross-sectional design. The sample in this study consisted of 80 respondents selected using non-probability sampling with consecutive sampling. Data were collected using observation sheets and analyzed using the Chi-Square test. This study found that there was a relationship between sitting position and changes in blood pressure during spinal anesthesia induction, with a p-value of < 0.001.